SEJARAH PERKEMBANGAN ISLAM DI TURKI - Rahman, Fathur (Tasamuh: Jurnal Studi Islam, 2018)
Over the hundreds of years, Islam have been growing rapidly in Turkey. Although the majority of its people are Muslims, in its development, Turkey became a republic with a secular democratic state system. In this paper will be reviewed the history of Islamic development in Turkey, including developments in the reform era that makes Turkey as it is today, the country that constructs Islam as a rational and scientific religion.The history of Turkey is divided into five periods. The first period, ie in 1299-1402, begins with the founding of the Ottoman empire. The Second Period, 1402-1566, is marked by royal restoration. The third period, 1566- 1699, was marked by the Ottoman ability to defend its territory. The fourth period, the year 1699-1838, marked degan gradually subside of the kingdom then experience more progress. The fifth period, 1839-1922, was marked by a cultural revival and Turkey became a republic, and it was no longer a system of government based on empire, dynasty, or caliphate as it had been for centuries. Mustafa Kemal established Turkey as a secular modern state based on its disappointment with the previous Caliphate system. In the latter period also called the contemporary era, although acknowledged as a secular republic, the Turkish government supports the implementation of Friday prayers in the mosque as a form of social discipline. Likewise, fasting to build patience and patience, andÂ paying zakat encourages ones generosity, the birth of Islamic parties; moral enforcement and social justice; banning polygamy and divorce decisions must be made in court; equal rights of women and men in education, work, and in politicsâin 1934 women were given the right to be nominated in national elections.